Geographic Comparison of Women in Academic Obstetrics and Gynecology Department-Based Leadership Roles. Issue 4 (October 2017) - Ricciotti, Hope A.; Dodge, Laura E.; Aluko, Ashley; Hofler, Lisa G.; Hacker, Michele R.
Abstract : OBJECTIVE: To describe and compare geographic representation of women in obstetrics and gynecology department-based leadership roles across American Congress of Obstetricians and Gynecologists (ACOG) districts and U.S. Census Bureau regions while accounting for the proportion of women practicing in each area. METHODS: We conducted a cross-sectional observational study. To more meaningfully quantify representation of women as leaders in ACOG districts and U.S. Census Bureau regions, we calculated representation ratios—the proportion of department-based leaders who were women divided by the proportion of obstetrician–gynecologists who were women. A ratio of 1.0 indicates proportionate representation and less than 1.0 indicates underrepresentation. We calculated 95% CIs to compare representation of women in leadership roles across geographic areas. The gender of major department-based leaders (chair, vice chair, division director) and educational leaders (fellowship, residency, associate residency, medical student clerkship director) was determined from websites. RESULTS: The proportion of department chairs who were women was highest in the West and lowest in the South Census Bureau regions. Representation ratios for women in major department-based leadership roles demonstrated underrepresentation relative to the practicing base nationally and in all four regions. Although women were underrepresented in major department-based leadership throughout the country, there was significantly higher women's representation in major department-based leadership roles in the West (ratio 0.82, 95% CI 0.68–0.99) compared with the Northeast (ratio 0.50, 95% CI 0.42–0.59) and the South (ratio 0.45, 95% CI 0.36–0.57). Similarly, in the division director role, the West (ratio 0.85, 95% CI 0.68–1.1) had significantly higher representation of women compared with the Northeast (ratio 0.50, 95% CI 0.40–0.62). Nationally, women were underrepresented as fellowship directors, proportionately represented as residency program directors, and overrepresented as medical student clerkship directors. CONCLUSION: Representation ratios of women in major department-based leadership roles, which account for the proportion of women practicing in each geographic area, suggest that women were more likely to advance to the department-based leadership roles of chair, vice chair, or division director in the western United States. Abstract : Women are more likely to advance to obstetrics and gynecology department-based leadership roles of chair, vice chair, and division director in the West.